The cathodic deprotection of the nitrobenzoyl group from phenyl nitrobenzoates in N,N-dimethylformamide - Jorge, SMA; Stradiotto, N. R. (Elsevier B.V., 1997)
The reduction of phenyl benzoates with nitro substituents at the 2-,3- and 4-positions of the benzoates in N,N-dimethylformamide is reported. The phenyl 4- and 3-nitrobenzoate are reduced in two cathodic steps. The first one, at about -0.9 V vs. SCE, a reversible one-electron process, gives a rather stable anion radical. The second reduction step at potentials between -1.5 and -2.0 V vs. SCE leads to formation of the dianion, which decomposes giving free phenol in good yields (> 80%). on the other hand, the phenyl 2-nitrobenzoate is reduced in one cathodic step. This step occurs at -0.9 V with formation of an unstable anion radical which decomposes via C-O bond cleavage, giving phenol with a yield of ca. 80%. The mechanisms of the reduction of these compounds are discussed. (C) 1997 Elsevier B.V. S.A.
Keywords: phenyl nitrobenzoates; cathodic deprotection; nitrobenzoyl group